Knowledge Processing and Data Analysis First International Conference, KONT 2007, Novosibirsk, Russia, September 14-16, 2007 and First International Conference, KPP 2007,Darmstadt, Germany, September 28-30, 2007. Revised Selected Papers - Wolff, Karl Erich; Palchunov, Dmitry E.; Zagoruiko, Nikolay G.; Andelfinger, Urs.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the First International Conference on Knowledge - Ontology - Theory (KONT 2007) held in Novosibirsk, Russia, in September 2007 and the First International Conference on Knowledge Processing in Practice (KPP 2007) held in Darmstadt, Germany, in September 2007. The 21 revised full papers were carefully reviewed and selected from numerous submissions and cover four main focus areas: applications of conceptual structures; concept based software; ontologies as conceptual structures; and data analysis.
Keywords: Computer science; Database management; Information storage and retrieval systems; Artificial intelligence; Computational linguistics; Computer Science; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Database Management; Mathematical Logic and Formal Languages; Computational Linguistics; Computer Science, general